Revealing the history of ancient palestine - Whitelam, Keith W., author.
1 online resource (334 pages)
Keywords: This volume is part of the Changing Perspectives sub-series, which is constituted by anthologies of articles by world-renowned biblical scholars and historians that have made an impact on the field and changed its course during the last decades. This volume offers a collection of seminal essays by Keith Whitelam on the early history of ancient Palestine and the origins and emergence of Israel. Collected together in one volume for the first time, and featuring one unpublished article, this volume will be of interest to biblical and ancient Near Eastern scholars interested in the politics of historical representation but also on critical ways of constructing the history of ancient Palestine.